Data on Germs Patterns and Sensitivity to Antibiotics in Late Onset Ventilator Associated Pneumonia at ICU Haji Adam Malik Hospital Medan 2024 - Dwisa Febrina Ritonga; Fajrinur Syarani; Syamsul Bihar; Taufik Ashar (Jurnal Multidisiplin Indonesia, 2026)
Ventilator-associated pneumonia (VAP) is a lung infection that occurs in patients using mechanical ventilators for more than 48 hours, with late-onset VAP posing a high risk of multidrug-resistant pathogens. Data on bacterial patterns and antibiotic sensitivity are crucial for empirical treatment and resistance control. This research aims to identify bacterial patterns and antibiotic sensitivity in late-onset VAP cases at the ICU of Haji Adam Malik Hospital, Medan, in 2024. A cross-sectional study was conducted involving 76 samples. Demographic data, bacterial cultures, and antibiotic sensitivity results, obtained from medical records, were analyzed using SPSS 22.0. Among 75 patients with late-onset VAP, the majority were over 50 years old (63.2%) and male (57.9%). Acinetobacter baumannii (44.7%) and Pseudomonas aeruginosa (15.8%) were the most common pathogens. High resistance to cephalosporins was noted, while colistin, polymyxin B, amikacin, and norfloxacin remained effective. A significant association was found between VAP incidence and the duration of ventilator use (p < 0.001). Acinetobacter baumannii is the dominant pathogen in late-onset VAP, with significant antibiotic resistance. Continuous surveillance of bacterial profiles and resistance patterns is essential to guide effective empirical therapy and infection control.